Why we read fiction : theory of mind and the novel - Zunshine, Lisa (Theory and interpretation of narrative series., 2006)
Why We Read Fiction offers a lucid overview of the most exciting area of research in contemporary cognitive psychology known as "Theory of Mind" and discusses its implications for literary studies. It covers a broad range of fictional narratives, from Richardson s Clarissa, Dostoyevski's Crime and Punishment, and Austen s Pride and Prejudice to Woolf's Mrs. Dalloway, Nabokov's Lolita, and Hammett s The Maltese Falcon. Zunshine's surprising new interpretations of well-known literary texts and popular cultural representations constantly prod her readers to rethink their own interest in fictional narrative. Written for a general audience, this study provides a jargon-free introduction to the rapidly growing interdisciplinary field known as cognitive approaches to literature and culture.